2014
DOI: 10.5194/amt-7-1861-2014
|View full text |Cite
|
Sign up to set email alerts
|

Variable anisotropy of small-scale stratospheric irregularities retrieved from stellar scintillation measurements by GOMOS/Envisat

Abstract: Abstract. In this paper, we consider possibilities for studying the anisotropy of small-scale air density irregularities using satellite observations of bi-chromatic stellar scintillations during tangential occultations. Estimation of the anisotropy coefficient (the ratio of the characteristic horizontal to vertical scales) and other atmospheric parameters is based on the comparison of simulated/theoretical and experimental autospectra and coherency spectra of scintillation. Our analyses exploit a 3-D model of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
11

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
7
0
11
Order By: Relevance
“…As noted in Sect. 2.1, observations of stellar occultations with grazing geometry (Kan et al, 2014), together with the data about the anisotropy of dominant IGWs (e.g., Ern et al, 2004, the description of CRISTA experiment) and GPS occultations in Wang and Alexander (2010) have revealed that the anisotropy coefficient is not uniform. It increases from about 10-20 for the IGW breaking scale (10-20 m in the vertical direction) to the saturation value of several hundred for dominant IGWs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in Sect. 2.1, observations of stellar occultations with grazing geometry (Kan et al, 2014), together with the data about the anisotropy of dominant IGWs (e.g., Ern et al, 2004, the description of CRISTA experiment) and GPS occultations in Wang and Alexander (2010) have revealed that the anisotropy coefficient is not uniform. It increases from about 10-20 for the IGW breaking scale (10-20 m in the vertical direction) to the saturation value of several hundred for dominant IGWs.…”
Section: Discussionmentioning
confidence: 99%
“…We will use a model of the IGW spectrum with a constant anisotropy η = const 1, although the latest studies of stellar scintillations (Kan et al, 2012(Kan et al, , 2014 indicate that the anisotropy increases and saturates with increasing scale; the saturation value being about 100 for vertical scales of about 100 m. We will show that RO signal fluctuations are determined primarily by the Fresnel scale ρ F and the outer scale L. For radio waves with λ = 20 cm at a GPS-LEO path, ρ F equals about 1 km, while the vertical outer scale L W is several kilometers. For inhomogeneities with scales ≥ 1 km, the anisotropy η significantly exceeds its critical value η cr = √ R e /H 0 ≈ 30, where R e is the Earth's radius, and H 0 = 6-8 km is the atmospheric-scale height (Gurvich and Brekhovskikh, 2001).…”
Section: -D Models Of Refractivity Fluctuation Spectramentioning
confidence: 99%
“…It turned out that this correction is almost perfect when the star sets along the orbital plane but does not work properly for very oblique occultations due to the presence of residual scintillation caused by horizontal turbulent structures. Photometer data have also been used to investigate atmospheric turbulence (Kan et al, 2014) and to derive high-resolution temperature profiles (Dalaudier et al, 2006) from the time delay induced by chromatic refraction. Here we focus on the low-frequency part of the refractive effects by showing how to apply the ARID algorithm to the photometer data for the retrieval of refractive angle profiles.…”
Section: Gomos Instrumentsmentioning
confidence: 99%
“…The subject of stellar scintillations is very broad and directly related to the study of atmospheric turbulence (Wheelon, 2001(Wheelon, , 2003. Star occultations have been the main technique used by the GOMOS instrument and allowed the reconstruction of atmospheric irregularities in air density and temperature profiles (see Kan et al (2014) and reference therein).…”
Section: Introductionmentioning
confidence: 99%
“…We will use a model of the IGW spectrum with a constant anisotropy η = const ≫ 1, although the latest studies of stellar scintillations (Kan et al, 2012(Kan et al, , 2014 indicate that the anisotropy increases and saturates with increasing scale; the saturation value being about 100 for vertical scales of about 100 m.…”
mentioning
confidence: 99%